(untitled) (World Economics and Finance Bulletin, 2026)
The article examines the role of human capital as a key factor in sustainable economic growth in the Republic of Uzbekistan. Based on the analysis of strategic documents, data from international organizations and statistical reports, the author considers the theoretical foundations of the relationship between human capital and economic development, as well as the practical aspects of implementing public policy in this area. Particular attention is paid to the analysis of the dynamics of the World Bank Human Capital Index and the UNDP Human Development Index, assessing the effectiveness of investments in education and healthcare, as well as the problems and prospects for the development of human capital in the context of the implementation of the updated Strategy "Uzbekistan 2030". The work identifies the main achievements (reduction of the poverty rate to 5.8%, GDP growth, increase in investment in the social sphere) and systemic challenges (insufficient quality of education, persistent regional disparities, "brain drain") that hinder the realization of human potential. Based on the analysis, recommendations are formulated for improving public policy in the field of human capital development